Evaluation on Infectivity of Babesia microti to Domestic Animals and Ticks Outside the Ixodes Genus - Wu, Jiajun; Cao, Jie; Zhou, Yongzhi; Zhang, Houshuang; Gong, Haiyan; Zhou, Jinlin (Frontiers in Microbiology, 2017)
Babesiosis caused by Babesia microti parasite is an emerging tick borne zoonotic disease that was confirmed recently in China. To understand the epidemiology characteristics of this emerging disease, infectivity of B. microti to domestic animals and ticks outside the genus Ixodes was evaluated in this study. Different domestic animals, chick, pig, goat, dog and the reference host rat were experimentally inoculated with B. microti-infected erythrocytes and the parasite infection was monitored daily by blood smear observation, real-time PCR detection, nested-PCR and special antibody responses during 55 days period. The results showed that rats infected with B. microti showed a typical sustained infection with strongly antibody responses; however, both goats and dogs infected with B. microti only showed transient antibody responses and the parasite was not found by blood smear observation or PCR; neither the parasite nor the special antibodies were detected in experimental chicks and pigs. On the other hand, the present study also experimentally investigated the infectivity of B. microti to Rhipicephalus haemaphysaloides, Haemaphysalis longicornis and Hyalomma asiaticum three species of ticks outside the genus Ixodes and the transmission experiment of B. microti between H. longicornis ticks and mice. Results showed that B. microti can be detected in the nymph and adult of these species after molting from engorged tick fed on infected mice, but the parasite was not detected in larvae hatching from eggs of engorged female tick fed on the infected mice. Transmission of B. microti to mice by infected H. longicornis nymphs was confirmed. These results indicated that these domestic animals do not have reservoir competence for B. microti, however, three species of ticks out of the genus Ixodes, common in China were successfully infected by B. microti, with H. longicornis showing the potential of transmitting the parasite to the vertebrate host.